Challenges and Strategies in Online Learning Process During Covid-19 Pandemic: The Students' Voice - ERIZA PUSPITA (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of this study was to find out students' opinions about the challenges they face in the online learning process during Covid-19, as well as to find out what strategies students use in overcoming the challenges they face. This research method uses descriptive qualitative. The subjects of this study were taken from 4 2nd semester students from the English Department of UNISMA. Researchers used online interviews to obtain the data needed in this study. The theory of data collection in this study uses the theory of Miles & Huberman (2013) where in theory there are 3 ways of collecting data, namely data reduction, data analysis, and drawing conclusions. The results of this study indicate that students face many challenges or difficulties in the online learning process during the Covid-19 pandemic such as limited internet, signal interference, difficulty understanding material, and boredom and laziness when studying online. In addition, the researchers also found strategies used by students in overcoming these challenges.Keywords: Challenges, Strategies, Online Learning